Evaluation of the Use of Remodelable Pericardial Bolsters during Cystectomy and Diversion to Prevent Enterocutaneous Fistulas. Issue 3 (May 2018) - Krughoff, Kevin; Ha, Sarah; Crawford, David; Wilson, Shandra
Abstract : Introduction: : Enterocutaneous fistula is one of the most serious and potentially devastating complications after radical cystectomy, a complex operation with a significant morbidity rate. In this analysis we examined the potential benefit of biomaterial buttressing of staple lines in reducing the incidence of enterocutaneous fistula in patients undergoing cystectomy. Methods: : We retrospectively reviewed 398 patients undergoing cystectomy for bladder cancer during an approximately 11‐year period at the University of Colorado Hospital, and compared the frequency of enterocutaneous fistula before and after the implementation of biomaterial buttressing for bowel anastomosis. Results: : In total, 301 surgical cases preceded biomaterial buttressing and 97 received buttressing with bovine pericardial strips. Seven cases (2.3%) of enterocutaneous fistula occurred without adjunctive reinforcement whereas zero cases were identified in the period using buttressing with bovine pericardial strips. Thus buttressing was associated with a nonsignificant reduction in the odds of enterocutaneous fistula (OR 0.20; 95% CI 0.01, 3.56; p=0.20). Although risk factor adjustment was prohibited by the low frequency of events, none of the cases of enterocutaneous fistula had received prior radiation therapy. Incidentally, the odds of postoperative functional bowel obstruction were significantly decreased after the implementation of buttressing (OR 0.28; 95% CI 0.08, 0.93; p=0.03). Conclusions: : The absolute reduction in the incidence of enterocutaneous fistula and significantly decreased odds of functional bowel obstruction in this cohort warrant future investigation to confirm the benefit of bovine pericardial strip buttresses for bowel anastomoses in cystectomy.